If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4n + 3)(n + 9) = 0 Reorder the terms: (3 + 4n)(n + 9) = 0 Reorder the terms: (3 + 4n)(9 + n) = 0 Multiply (3 + 4n) * (9 + n) (3(9 + n) + 4n * (9 + n)) = 0 ((9 * 3 + n * 3) + 4n * (9 + n)) = 0 ((27 + 3n) + 4n * (9 + n)) = 0 (27 + 3n + (9 * 4n + n * 4n)) = 0 (27 + 3n + (36n + 4n2)) = 0 Combine like terms: 3n + 36n = 39n (27 + 39n + 4n2) = 0 Solving 27 + 39n + 4n2 = 0 Solving for variable 'n'. Factor a trinomial. (9 + n)(3 + 4n) = 0Subproblem 1
Set the factor '(9 + n)' equal to zero and attempt to solve: Simplifying 9 + n = 0 Solving 9 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + n = 0 + -9 Combine like terms: 9 + -9 = 0 0 + n = 0 + -9 n = 0 + -9 Combine like terms: 0 + -9 = -9 n = -9 Simplifying n = -9Subproblem 2
Set the factor '(3 + 4n)' equal to zero and attempt to solve: Simplifying 3 + 4n = 0 Solving 3 + 4n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4n = 0 + -3 4n = 0 + -3 Combine like terms: 0 + -3 = -3 4n = -3 Divide each side by '4'. n = -0.75 Simplifying n = -0.75Solution
n = {-9, -0.75}
| b+b+b+22=b+b+6 | | 4x+4=-7+2x+25 | | -7(-2-6b)+9b= | | 12p+3=30 | | pie=7.3m | | 2u-10=0 | | 2w+3.7=0.5 | | 13x-34=10x-10 | | (b-7)(b+3)=0 | | 2u-10=14 | | 800=16n^2+56n | | (x+20)+7=20 | | 3x+8+8y=15 | | 4d-3+2d=9 | | 2x+y=532 | | 1.25+-3= | | 17-s/4-10 | | 9+m=27+27 | | -6(x-2)-26=-14 | | 5*sin(x)+2=sin(x) | | 7n-54=2n+56 | | 5=2+3u | | (-3x+3y)(9x^2+9xy+9y^2)= | | 8+8w+(27+9w)=0 | | 20/25= | | 23x+23=34 | | 3(3x-1)-3(2x)=1 | | 3n+35= | | 0.9x-2.1-0.9=0.2(5-x) | | 0.029x+2=0.034x | | 7(y-6)+3y=10(y+1) | | 11+18=x+19 |